Course of COVID-19 in Patients with Inflammatory Bowel Disease: Regional Experience - L. M. Kupkenova; E. N. Belousova; E. S. Bodryagina; D. D. Mukhametova; A. Kh. Odintsova; D. G. Iskhakova; D. I. Abdulganieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to study the course of COVID-19 in patients with inflammatory bowel diseases (IBD) using the example of the region of the Republic of Tatarstan.Material and methods. The study included 101 patients diagnosed with IBD and COVID-19, who were observed in two infectious diseases hospitals in Kazan (Republican Clinical Hospital of the Ministry of Health of the Republic of Tatarstan and City Clinical Hospital No. 7) and on an outpatient basis from April 2020 to March 2022. All patients underwent physical examination, laboratory and instrumental diagnostic methods, including a PCR test for SARSCoV-2. Chest computed tomography was performed in patients with clinical signs of moderate to severe COVID-19.Results. Ulcerative colitis (UC) was diagnosed in 60 (59.4 %) patients, Crohn's disease (CD) — in 41 (40.6 %) patients. The mean age of the patients was 41.0 ± 14.7 years, of which 59 (58.4 %) were men and 42 (41.6 %) were women. A comparative analysis of patients with and without IBD and CT-verified lung disease was carried out. It was found that the development of viral pneumonia was influenced by age over 55 years (39.2 ± 9.7 vs. 46.3 ± 10.6, p < 0.05), increased Body Mass Index (BMI) (23.1 ± 5.35 vs. 30.25 ± 6.17, p < 0.05), hypertension (6 (8.3 %) vs. 8 (27.6 %), p < 0.05), diabetes mellitus (2 (2.7 %) vs. 5 (17.2 %), p < 0.05), the use of corticosteroids in the treatment of IBD (8 (11.1 %) vs. 10 (34.5 %), p < 0.05). In a comparative analysis of patients with IBD and COVID-19 from the SECURE-IBD database and own data, it was found that the average age of patients was comparable (42.7 vs 41.0). At the same time, in our group of male patients, there were slightly more people with DM, increased BMI, and an active course of IBD. The proportion of hospitalized patients was higher. In our cohort, there were fewer patients receiving biological therapy, but more patients on 5-aminosalicylic acid (5-ASA) and systemic corticosteroids. At the same time, lethal outcomes were comparable.Conclusion. In patients with IBD, the development of viral pneumonia was influenced by known risk factors for COVID-19: age over 55 years (p < 0.05, odds ratio (OR) 3.153), increased BMI (p < 0.05, OR 1.667), hypertension  (p < 0.05, OR 2.724), diabetes (p < 0.05, OR 1.489), as well as the use of systemic corticosteroids (p < 0.05, OR 1.5).